The effects of music listening intervention on postoperative care in unilateral vs. bilateral endometriotic cysts - Yang, Xiaohui; Meng, Yue; Feng, Huiyan; Long, Ya; Zheng, Zhijia; Li, Xiaomao; Ye, Qingjian (Frontiers in Medicine, 2025)
BackgroundEndometriosis is a chronic gynecological condition that can result in pelvic pain and infertility, thereby significantly impacting women's reproductive health. Psychological disorders such as anxiety and depression are common in women with endometriosis and can have a detrimental effect on their quality of life. Conventional postoperative care primarily focuses on medical and surgical aspects; however, there is a growing need to address the psychological wellbeing of patients as part of comprehensive postoperative care. Music listening interventions have emerged as a promising adjunctive approach due to their non-invasive and non-pharmacological nature, which can potentially enhance the postoperative experience by targeting both physical and psychological aspects.MethodsThis study is a secondary analysis of a randomized controlled trial with 141 young nulliparous participants who underwent laparoscopic endometriosis cyst resection at Sun Yat-sen University's Third Affiliated Hospital from September 2023 to August 2024. Participants were divided into a music listening group (n = 72) and a control group (n = 69). The music listening group received 30-min daily sessions starting the day before surgery for 7 days.Results141 patients were categorized into two groups: the unilateral cyst group (93 patients) and the bilateral cyst group (48 patients). In both unilateral and bilateral cyst cohorts, the intervention failed to demonstrate efficacy in reducing postoperative nausea/vomiting or pain intensity (all P > 0.05). Similarly, anxiety (GAD-7), depression (PHQ-9), and fatigue (FSS) scores showed no significant improvements in either subgroup at any postoperative assessment (all P > 0.05). A transient reduction in anxiety (GAD-7) was observed in bilateral cyst patients at day 7 (P = 0.046), but this effect lost significance after Bonferroni correction (adjP = 0.460). Longitudinal changes in psychological scores from baseline to postoperative days 1–7 were also non-significant.ConclusionThis secondary analysis indicates that a 7-day music listening intervention (30 min/day) doesn't confer significant benefits for postoperative pain, nausea/vomiting, anxiety, depression, or fatigue in young nulliparous patients undergoing laparoscopic endometriotic cystectomy, irrespective of unilateral or bilateral cyst involvement. Future studies should investigate optimized protocols (e.g., therapist-guided sessions, longer duration) and mechanistic biomarkers to identify potential responders.